2017
DOI: 10.1080/15332985.2017.1385565
|View full text |Cite
|
Sign up to set email alerts
|

Timing of housing crises: Impacts on maternal depression

Abstract: Housing problems threaten maternal mental health, but the nature of the relationship between housing and depression across time is not fully understood. Drawing upon the literatures of household shocks and depressive illness, the present study leveraged longitudinal data from the Fragile Families and Child Well-Being Study to probe the relationship between a housingrelated crisis and depression among at-risk mothers ( = 2,503). Binary logistic regression tested whether a housing crisis predicted an episode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Many studies on teen depression symptoms and maternal depression symptoms have shown teen and maternal socioeconomic characteristics and experiences, such as social support, employment, and housing (Cairney et al, 2003;Fowler et al, 2015;Marcal, 2018), as well as their environmental stressors, including potential ongoing exposure to a violent partner Journal of Interpersonal Violence (Levendosky et al, 2002;Johnson et al, 2014;Sternberg et al, 2006), made differences on the outcome variables. This study applies longitudinal data collected across 15 years and aims to examine the long-term effects of IPV, as well as the temporal sequence of such effects, to explain how IPV experienced by the mother during pregnancy may affect teen depression through maternal depression and parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on teen depression symptoms and maternal depression symptoms have shown teen and maternal socioeconomic characteristics and experiences, such as social support, employment, and housing (Cairney et al, 2003;Fowler et al, 2015;Marcal, 2018), as well as their environmental stressors, including potential ongoing exposure to a violent partner Journal of Interpersonal Violence (Levendosky et al, 2002;Johnson et al, 2014;Sternberg et al, 2006), made differences on the outcome variables. This study applies longitudinal data collected across 15 years and aims to examine the long-term effects of IPV, as well as the temporal sequence of such effects, to explain how IPV experienced by the mother during pregnancy may affect teen depression through maternal depression and parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers reported whether they had difficulty affording rent, mortgage, or utility payments; had been evicted for nonpayment of rent; had moved in with friends or family members to avoid becoming homeless; or spent time living in a homeless shelter or on the street. Although no standard definition of housing instability exists, similar indicators have been utilized in other studies of vulnerable families to capture a range of housing-related risk (Marcal, 2018; Ma, Gee, & Kushel, 2008; Park et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…A further consideration is that risks to parental mental health are increased, especially among single mothers, given that housing instability is associated with an increased risk of depression in mothers. 7 Finally, existing vulnerabilities and risk factors for safeguarding are exacerbated by additional factors introduced by the pandemic.…”
Section: Impacts Of Covid-19 On Vulnerable Children In Temporary Accommodation In the Ukmentioning
confidence: 99%